2021
DOI: 10.1029/2020jd033356
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Chemical and Mineral Compositions on the Parameterization of Immersion Freezing by Volcanic Ash Particles

Abstract: Volcanic ash (VA) from explosive eruptions contributes to aerosol loadings in the atmosphere. Aside from the negative impact of VA on air quality and aviation, these particles can alter the optical and microphysical properties of clouds by triggering ice formation, thereby influencing precipitation and climate. Depending on the volcano and eruption style, VA displays a wide range of different physical, chemical, and mineralogical properties. Here, we present a unique data set on the ice nucleation activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 122 publications
0
6
0
Order By: Relevance
“…The choice of gas used for adsorption may represent a source of uncertainty in this approach as gases may differ in their interactions with particle surfaces. Ice nucleation studies have used nitrogen, water vapor and argon gas to quantify the specific surface area (Hiranuma et al, 2015;Umo et al, 2021). While Hiranuma et al (2015) found only minor differences between the specific surface areas of illite samples measured using nitrogen and water vapor, other aerosol types may exhibit different behavior due to differences in physicochemical surface properties and morphology.…”
Section: Uncertainties Associated With the Aerosol Size Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of gas used for adsorption may represent a source of uncertainty in this approach as gases may differ in their interactions with particle surfaces. Ice nucleation studies have used nitrogen, water vapor and argon gas to quantify the specific surface area (Hiranuma et al, 2015;Umo et al, 2021). While Hiranuma et al (2015) found only minor differences between the specific surface areas of illite samples measured using nitrogen and water vapor, other aerosol types may exhibit different behavior due to differences in physicochemical surface properties and morphology.…”
Section: Uncertainties Associated With the Aerosol Size Distributionmentioning
confidence: 99%
“…The choice of gas used for adsorption may represent a source of uncertainty in this approach as gases may differ in their interactions with particle surfaces. Ice nucleation studies have used nitrogen, water vapor and argon gas to quantify the specific surface area (Hiranuma et al., 2015; Umo et al., 2021). While Hiranuma et al.…”
Section: Ice Nucleation Parameterizationsmentioning
confidence: 99%
“…Various inorganic and (bio)­organic materials in the environment may act as ice nucleating entities. , For instance, biological substances (e.g., Pseudomonas syringae) are highly efficient (∼ −2 to −4 °C), while nonbiological substances (e.g., Gypsum) tend to exhibit less efficient ice-nucleating capabilities (−16 to −21 °C). Volcanic ash particles have been shown to nucleate via the immersion freezing mode within a temperature range of −10 to −35 °C, and the ice nucleation active site densities range from 10 5 to 10 11 m –2 , respectively. , The soil dust achieves this ice activity at about −10 °C, because the ice nucleation efficiency (INE) starts to decrease at temperatures greater than −10 °C. Hill et al have reported that, at temperatures greater than −10 °C, most soils in arable lands achieve 10 6 per gram.…”
Section: Introductionmentioning
confidence: 96%
“…Volcanic ash particles have been shown to nucleate via the immersion freezing mode within a temperature range of −10 to −35 °C, and the ice nucleation active site densities range from 10 5 to 10 11 m −2 , respectively. 9,10 The soil dust achieves this ice activity at about −10 °C, because the ice nucleation efficiency (INE) starts to decrease at temperatures greater than −10 °C. Hill et al 11 have reported that, at temperatures greater than −10 °C, most soils in arable lands achieve 10 6 per gram.…”
Section: Introductionmentioning
confidence: 99%
“…The physicochemical properties and atmospheric lifetime of these aerosols modulate their interactions with clouds and radiation. For example, aged ash (coated with sulfate) differs from fresh ash (noncoated) not only in the optical properties (Muser et al., 2020) but also by affecting the ice and cloud nucleation (Maters et al., 2020; Umo et al., 2021). To improve our understanding of the impact volcanic eruptions can have on local and global weather, it is essential to constrain the processes that affect the properties and lifetime of volcanic aerosols (e.g., von Savigny et al., 2020).…”
Section: Introductionmentioning
confidence: 99%